Reengineering Leadership Competencies According to Some Contemporary Leadership Trends: Field Study on Leaders in the Ministry of Education – Kuwait - Alghadhouri, Hanan Mohammed (Journal of Educational and Psychological Sciences, 2020)
The study aims to reveal the leadership competencies reengineering according to some contemporary leadership trends – a field study on the ministry of education leaders– Kuwait. The study adopted the evolutionary survey method since it’s suitable for the purposes of the present study, and the study based on the questionnaire to collect data. The study sample consisted of (260) individuals; all administrators, department heads, officials, and school headmasters working in Kuwaiti Ministry of Education. The study found that the degree of Reengineering Leadership Competencies in the Managers of Kuwaiti Ministry of Education according to some leadership was (2.71 out of 5.00) which of medium level. On the dimensional level; the dimension of the elements of reengineering is the highest mean (2.83), followed by the performance rate rise with mean of (2.70) and finally the infrastructure engineering dimension with mean of (2.60), and all dimensions were in the (medium level). The results showed that there were statistically significant differences at the level of (0.05≥α) in the degree of leadership competencies availability in the Kuwaiti Ministry of Education managers attributed to the educational qualification and the variance was in favor of PhD category. The study recommended that innovation should be activated among managers and decision-makers to form modern strategic plans in the Kuwaiti Ministry of Education.